IMPLEMENTASI PENEGAKAN HUKUM TINDAK PIDANA PERUNDUNGAN (BULLYING) OLEH ANAK DI KOTA WATAMPONE - Fathurrahman Salewangeng, Muh. Hasby; Muhadar, Muhadar; Azisa, Nur (UNES Law Review, 2023)
From 2011 to 2015 at least 1,850 cases of bullying occurred at school and outside school. This research reviews two problems, How is the enforcement implementation of law enforcement of criminal disputes (bullying) by children in Watampone towns and any factors that hinder the implementation of law enforcement (bullying) by children in the city of Watampone. The kind of research used is empirical legal studies or research law sociological or research field law. Reviewed from the number of cases bullying by high-counted children despite efforts such as bullying-related counseling at school. This can be concluded that the case of bullying by the child was not found at the watampone state court compared to the number of cases existing. The factors that hamper law enforcement ( bullying ) perundungan crimes by children in a city watampone not run according to the rules and the law, the law enforcement, the facilities and infrastructure, the people and the culture. Reviewed by the enforcement factor of bullying by children in the city of Watampone, the surrounding environment should pay more attention to the behavior of children so that they do not trigger the occurrence of bullying by children.